2017
DOI: 10.4085/1062-6050-51.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainer Services in Public and Private Secondary Schools

Abstract: Context: The presence of athletic trainers (ATs) in secondary schools to provide medical care is crucial, especially with the rise in sports participation and resulting high volume of injuries. Previous authors have investigated the level of AT services offered, but the differences in medical care offered between the public and private sectors have not been explored. Objective: To compare the level of AT services in public and private secondary schools.Design: Concurrent mixed-methods study. Setting: Public an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 13 publications
4
63
1
Order By: Relevance
“…Just over half of high school coaches reported that an AT was present at their practices at least some of the time versus nearly 80% who stated that an AT was present at their competitions at least some of the time. These coverage levels are similar to those observed earlier [5][6][7][8]30,31 : between 34% and 70% of high schools used the services of an AT, but the level of coverage provided (full time, part time, etc) varied widely based on school and community characteristics. Significant resources have been expended with the goal of increasing medical coverage at the secondary school level, and although improvements can still be made, these efforts have increased access to AT services in high schools during the past 20 years.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Just over half of high school coaches reported that an AT was present at their practices at least some of the time versus nearly 80% who stated that an AT was present at their competitions at least some of the time. These coverage levels are similar to those observed earlier [5][6][7][8]30,31 : between 34% and 70% of high schools used the services of an AT, but the level of coverage provided (full time, part time, etc) varied widely based on school and community characteristics. Significant resources have been expended with the goal of increasing medical coverage at the secondary school level, and although improvements can still be made, these efforts have increased access to AT services in high schools during the past 20 years.…”
Section: Discussionsupporting
confidence: 84%
“…Emergency preparedness and training of high school coaches have been investigated extensively. [6][7][8][9][11][12][13][14]20 However, to our knowledge, this is the first study to compare emergency preparedness and training among high school coaches and coaches of high school-aged club teams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In New Jersey, a survey reported about 95% of public secondary schools had certified athletic training services, of which 91% served the school full time (Pryor et al 2015). For comparison, 70% of U.S. public secondary schools had athletic training services, although only 37% of them served the schools full-time (Pryor et al 2015;Adams et al 2019), and among public and private U.S. secondary schools combined about 58% had athletic training services, with 28% full-time (in NJ, 68 and 36%, respectively) (Pike et al 2017;Pike et al 2016). The present study, which had a greater involvement by certified ATCs than school nurses, documented a small difference in reporting symptoms by school nurses versus school ATCs.…”
Section: Discussionmentioning
confidence: 99%